HPLC–DAD Method for the Quantification of Carbamazepine, Oxcarbazepine and their Active Metabolites in HepaRG Cell Culture Samples - Ferreira, Ana (2016)
A new, sensitive and fast high-performance liquid chromatography–diode-array detection assay is herein reported, for the first time, to simultaneously quantify carbamazepine (CBZ), oxcarbazepine (OXC), and the active metabolites carbamazepine-10,11-epoxide (CBZ-E) and licarbazepine (LIC) in HepaRG cell culture medium samples. Chromatographic separation of analytes (CBZ, CBZE, OXC, LIC) and internal standard (IS) was achieved in less than 15 min on a C18-column, at 35 °C, using a mobile phase composed of water/methanol/acetonitrile (69:25:6 v/v/v) pumped at 1 mL min−1. The analytes and IS were detected at 215 nm. The method proved to be selective, accurate (bias ± 14.6 %), precise (coefficient of variation ≤13.1 %) and linear (r2 ≥ 0.9901) over the concentration ranges of 0.1–15 μg mL−1 for CBZ; 0.1–5 μg mL−1 for CBZ-E and OXC; and 0.1–40 μg mL−1 for LIC. Furthermore, the absolute recovery of the analytes ranged from 64.5 to 96.9 % and their stability was demonstrated in the studied conditions. This validated HPLC assay will be a suitable tool to support future in vitro metabolism profiling, drug interaction and other pharmacokinetic-based studies in HepaRG cells involving these antiepileptic drugs (CBZ and OXC) and their main metabolites.